The fantastic poetics and its modulation in Samanta Schweblin's "Pájaros en la boca" - Livellara Abrile, Julia (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Starting from what Jean-Marie Schaeffer in his theory on generic logics calls modulation, this article seeks to study the particular case of Samanta Schweblin in which these modulations of the fantastic genre have acquired great interpretative complexity and, nevertheless, do not fail to point out the presence of inherited antecedents. It is a way of approaching to a very current corpus without losing sight of the fact that recognizing the functioning of the fantastic genre in its previous instances is easier to identify a rigorous creation program that plays to destabilize the architecture by suppressing constituent elements that have been fundamental for the stability of the structure and today they are not; but they have been somehow beating in the absence. The objective is to corroborate whether the traces of this generic tradition remain in the present of literary reality and, more precisely, whether it is possible to speak of the actuality of the fantastic genre.
Keywords: generic logics, fantastic literature, Samanta Schweblin, literary tradition, argentinian literature.